The determinants of household saving in China: A dynamic panel analysis of provincial data - Charles Yuji Horioka; Junmin Wan (Osaka University, Institute of Social and Economic Research (ISER), 2006)
In this paper, we conduct a dynamic panel analysis of the determinants of the household saving rate in China using a life cycle model and panel data on Chinese provinces for the 1995-2004 period from China's household survey. We find that China's household saving rate has been high and rising and that the main determinants of variations over time and over space therein are the lagged saving rate, the income growth rate, (in many cases) the real interest rate, and (in some cases) the inflation rate. However, we find that the variables relating to the age structure of the population have the expected impact on the household saving rate in only one of the four samples. These results provide mixed support for the life cycle hypothesis as well as the permanent income hypothesis, are consistent with the existence of inertia or persistence, and imply that China's household saving rate will remain high for some time to come.
Keywords: D12; D91; E21; J10; 330; age structure; China; demographics; dependency ratio; habit formation; household saving; household saving rate; household; inertia; life cycle hypothesis; life cycle model; permanent income hypothesis; persistence; saving; saving rate; Privater Haushalt; Sparen; Lebensverlauf; China